Effect of Aromatic Massage on Somatic Problems among a Cohort of Menopausal Women - Nageya E. Said; Nabaweya S. Shehata; Sabah A. Abd El Haleem (Evidence-Based Nursing Research)
Context: Menopause is a significant event in women's lives. It marks the end of a woman's natural reproductive life; it is usually accompanied by symptoms that affect the women's ability to perform their normal daily activities. Massage is one of the non-pharmacological methods that can help women cope with menopausal symptoms.